The Relationship between the Role of Parents, Learning Style, and Use of Gadgets on Learning Outcomes, Physical Education, Sports and Health for Public Middle School Students in Semarang City - Naufal Najib, Afif; Sulaiman; Rahardjo, Agus (Journal of Physical Education and Sports, 2024)
Learning in the current era is closely related to digitalization. The role of parents, learning styles and use of gadgets will have a positive impact on students and support learning. The aim of this research is to determine the relationship between the role of parents, learning styles and use of gadgets on the learning outcomes of physical education, sports and health of state junior high school students in Semarang City. The research approach used was a quantitative method with a descriptive approach. Population and sample, namely a total of 280 respondents, 133 men and 147 women. The data analysis techniques in this research are correlation regression, data normality test, linearity test, homogeneity test and hypothesis test using SPSS version 23 software..The research results show that the relationship between the role of parents and learning outcomes has a sig value of 0.003 with a contribution of 20.2%. The relationship between learning styles and learning outcomes has a sig value of 0.007 with a contribution of 18.9%. The relationship between gadget use and learning outcomes has a sig value of 0.012 with a contribution of 31.4%. The relationship between the role of parents and learning styles on learning outcomes has a sig value of 0.001 with a contribution of 47.7%. The relationship between the role of parents and the use of gadgets on learning outcomes has a sig value of 0.002 with a contribution of 45.1%. The relationship between learning style and gadget use has a sig value of 0.033 on learning outcomes with a sig value of 0.001 with a contribution of 70.5%.